SACI: Sentiment Analysis by Collective Inspection on Social Media Content - Chaves, Rodrigo; Sá, Giovanni; Vieira, Ramon; Mourão, Fernando; Rocha, Leonardo (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2014)
Sentiment analysis on Social Media content represent a valuable information nowadays. Current studies assume that to determine a collective opinion requires the prior knowledge of each individual one. In this paper we present SACI (Sentiment Analysis by Collective Inspection), a lexicon-based unsupervised method that extracts collective sentiments without concerning about individual classifications. We demonstrate that SACI fulfills simultaneously requirements of efficacy and efficiency. Its collective analysis outperforms individual one w.r.t. approximating the collection sentiment. Further, a Web tool for real-time sentiment analysis built on the top of SACI demonstrates its usefulness.